SOME ASPECTS OF RUSSIAN-NOGAY RELATIONS IN THE XVI-XIX CENTURIES - A. Dzhumagulova (Гуманитарные и юридические исследования)
The article is devoted to the relationship between Russia and the Nogai societies that moved in the North Caucasus and the Northern Black sea region at the end of the XV-XIX centuries. The latter took an active part in political events related to the expansion of Russian influence in the East. The nature of this interaction is analyzed in historical retrospect, it is shown how the positions of the parties changed as a result of a dynamically changing geopolitical conjuncture. Particular attention is paid to the foreign policy aspects of the problem, which, in many respects, explain the positions of the parties in the process of building socio-political and cultural communication. Arguments are presented in favor of the hypothesis about the reason for the exodus of the Nogais to the territory of the Crimean Khanate, which, according to the author, was associated with the expansion of the Kalmyks to the Nogai nomads. The relations of the Nogais with the Crimean and Ottoman nobility were progressive only until the beginning of the attempts of the Crimean khans to establish political control in the Nogai hordes, using extremely harsh methods. Under such condi- tions, in the middle of the XVIII century, the Nogais began to look for a way out of onerous citizenship, the protection and patronage of the Russian Empire. The circumstances of the search for mutually acceptable forms of relations between the nomads and the imperial administration are shown. The places of residence of the main groups of the Nogai population are speciied, and those normative legal acts that underlie the regulation of the life of nomadic births are evaluated. The role of the institution of bailiff is shown as the most acceptable form of dialogue between the state and Nogai societies in the circumstances. The conclusion about the effectiveness of such a management model that allows unarmed methods to resolve emerging disputes is argued. The reasons for the exodus of a significant part of the Nogai nomads to the borders of Turkey are clariied, and the tragic fate of those migrants who chose to leave Russia is shown.